Correction: Anthocyanins from the fruits of Lycium ruthenicum Murray improve high-fat diet-induced insulin resistance by ameliorating inflammation and oxidative stress in mice. Issue 15 (1st July 2021) - Tian, Baoming; Zhao, Jianhua; Xie, Xiaoqing; Chen, Tao; Yin, Yan; Zhai, Ruohan; Wang, Xinlei; An, Wei; Li, Juxiu
Abstract : Correction for 'Anthocyanins from the fruits of Lycium ruthenicum Murray improve high-fat diet-induced insulin resistance by ameliorating inflammation and oxidative stress in mice' by Baoming Tian et al., Food Funct., 2021, 12, 3855–3871, DOI: ; 10.1039/D0FO02936J .